A novel ceramic coating for reduced metal ion release in metal‐on‐metal hip surgery. Issue 6 (17th November 2018) - Blunn, Gordon W.; Ferro De Godoy, Roberta; Meswania, Jayantilal; Briggs, Tim W. R.; Tyler, Philippa; Hargunani, Rikin; Wilson, Hannah; Khan, Imran; Marriott, Tim; Coathup, Melanie J.
Abstract: An ovine total hip arthroplasty model was developed to evaluate metal ion release, wear, the biological response and adverse tissue reaction to metal‐on‐metal (MoM) bearing materials. The performance of an advanced superlattice ceramic coating (SLC) was evaluated as a bearing surface and experimental groups divided into; (1) MoM articulating surfaces coated with a SLC coating (SLC‐MoM), (2) uncoated MoM surfaces (MoM), and (3) metal on polyethylene (MoP) surfaces. Implants remained in vivo for 13 months and blood chromium (Cr) and cobalt (Co) metal ion levels were measured pre and postoperatively. Synovial tissue was graded using an ALVAL scoring system. When compared with the MoM group, sheep with SLC‐MoM implants showed significantly lower levels of chromium and cobalt metal ions within blood over the 13‐month period. Evidence of gray tissue staining was observed in the synovium of implants in the MOM group. A significantly lower ALVAL score was measured in the SLC‐MoM group (3.88) when compared with MoM components (6.67) ( p = 0.010). ALVAL results showed no significant difference when SLC‐MOM components were compared to MoP (5.25). This model was able to distinguish wear and the effect of released debris between different bearing combinations and demonstrated the effect of a SLC coating when applied onto the bearing surface. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1760–1771, 2019.